The Effect of Use Of Matching Word Games Towards Students' Vocabulary Mastery At Mts Muhammadiyah Tanjung Belit Airtiris - Rodiyatul Fitri; Masrul Masrul; Citra Ayu (Universitas Muhammadiyah Enrekang, 2023)
This experimental research was carried out in eighth grade at MTs Muhammadiyah Tanjung Belit Airtiris. This research aims to determine the effect of the Matching Word Game on students' vocabulary mastery. This research methodology uses a quasi-experimental design. The sample for this research was class VII A as the experimental class and VII B as the control class. The experimental class consists of 17 students and the control class consists of 17 students. The instrument used in the research was a vocabulary test. Data were analyzed using the SPSS 25 program. Based on the research results, the average student score in the experimental class was 65.15 and 52.15 in the control class. Data analysis shows significance (2-tailed) 0000 < 0.05, which means Ha is accepted. It can be concluded that there is an influence on the use of the Matching Word Game on students' vocabulary mastery. Keywords: Vocabulary Mastery, Quasi Experimental, Matching Word Game.